VOCAL-MEDICAL: ON-LINE LANGUAGE LEARNING AND CULTURAL PREPARATION FOR EMERGENCY SERVICES - Brogan, Kristin; Adriaenssens, Jef; Kelly, Helen (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The VOCAL-Medical Project (Vocationally Oriented Culture and Language – Medical) is a two year Leonardo da Vinci Transfer of Innovation project, funded by the EU Commission, and part of the Lifelong Learning Programme. It follows on from two earlier EU projects, namely VOCAL (www.vocalproject.eu) and the award winning Problem-SOLVE. The VOCAL-Medical project partnership brings together 14 partner countries and 9 languages. The end product will be an on-line training tool for emergency staff who deal with patients who do not understand the local language. There will be also an app for mobile phones (smart phones) and tablets (with HTML5 functionalities) which can be used by the consultant in an emergency medical situation. This project is directed at professionals in the medical sector who need to communicate with patients who are non-nationals in emergency situations where good communication skills can literally mean the difference between life and death.It responds to a growing need in the medical sector to overcome the language andintercultural barriers which are occurring with ever greater frequency as a result of demographic changes and increased mobility. The project aims to bridge the gap between different healthcare systems and different cultural behaviours inherent in the doctor-patient relationship. This has benefits for healthcare systems, for the professionals who work in them and for patients. Resumen El Proyecto VOCAL-Medical (Vocationally Oriented Culture and Language – Medical / Cultura e Idioma Medico Orientado a la Formación Profesional Vocacional) es un proyecto de dos años del Leonardo da Vinci Transfer of Innovation (Transferencia de la Innovación), financiado por la Comisión Europea, dentro del Programa de Aprendizaje Permanente. (Lifelong Learning Programme). Es una continuación de dos anteriores proyectos de la UE: VOCAL (www.vocalproject.eu) y el ganador de premios Problem-SOLVE.